SAT0165 PERSPECTIVES OF WOMEN WITH CHRONIC RHEUMATIC DISEASES ON THEIR JOURNEY TO MOTHERHOOD: COMPARISON OF SURVEYS FROM ASIA-PACIFIC AND EUROPE. (June 2019) - Tanaka, Yoshiya; Barrett, Claire; Hirano, Yuji; Ikeda, Kei; Paizis, Kathy; Sameshima, Azusa; Su, Yu-Jih; Saadoun, Carine; Wong, Priscilla C.
Abstract : Background: The onset and diagnosis of chronic rheumatic disease (CRD) in women often overlap with their peak reproductive years. A previous survey 1 reported fears and misconceptions amongst women with CRD in Germany, France, UK, Italy and Spain (EU5) on their journey to motherhood. Objectives: To explore the perspectives of women with CRD in Asia-Pacific (APAC) regarding disease management and pregnancy, and the support they receive compared with patients in Europe. Methods: Women of childbearing age (18−45 years) with self-reported moderate to severe CRD (rheumatoid arthritis [RA], psoriatic arthritis [PsA], axial spondyloarthritis [axSpA]/ankylosing spondylitis [AS]) from Australia (AUS), Japan (JPN) and Hong Kong/Taiwan (HK/TW) completed a 20-min online survey (Sep−Nov 2018), similar to the previous EU5 survey. 1 Participants had been pregnant in the past 2–5 years. Results: 210 APAC participants had CRD (RA: n=122, PsA: n=48, axSpA/AS: n=40); 306 EU5 participants had CRD. Most APAC patients had moderate CRD (77%; severe: 23%). In their most recent pregnancy, 40% of the women were actively trying to get pregnant, 40% were neutral and 20% were either not thinking about a pregnancy or were actively trying to avoid it. Prior to pregnancy, more women consulted rheumatologists (62%) vs primary care physicians (26%) or OB/GYNs (20%; multiple responses were possible). Pregnancy planning was first discussed with a healthcare professional (HCP) at diagnosis (33%), at treatment initiation (32%) or during a regular visit (30%). Similar to EU5, discussions on family planning with HCPs in APAC were most often initiated by patients (Figure A ). APAC and EU5 patients delayed pregnancy for similar reasons including: fear of passing on health issues to their child, not feeling physically healthy enough to carry a child to term, not being emotionally ready to become a parent (Figure B). Antepartum, 55% of women reported disease improvement, 27% stable disease and 18% worsening disease activity. Compared with EU5, APAC women were less likely to have a treatment plan aligned between HCPs (APAC: 50%; EU5: 65%). The most frequently reported reasons for cessation of medications in pregnancy were 'worried about the treatment harming the foetus' (HK/TW: 68%; JPN: 59%; EU5: 54%) and 'switched to a safer treatment' (AUS: 52%). Similar to EU5, most women in APAC discussed breastfeeding with an HCP (>85%). However, whether women felt they had to decide between treatment and breastfeeding postpartum varied (HK/TW: 79%; EU5: 69%; JPN: 66%; AUS: 43%). Compared with EU5, fewer women in APAC felt they had all the information they needed on the impact of rheumatic disease and treatment on pregnancy and health (APAC: 34%; EU5: 56%). Conclusion: Fears and misconceptions about family planning, pregnancy and breastfeeding are common amongst women with CRD in APAC and Europe. In APAC, there may be a greater need for patient access to consistent and accurate information. Pregnancy planning with input from both physicians and obstetricians could alleviate patient concerns and minimise delays to pregnancy or treatment interruption. Reference: [1] Tincani A. ARD2018;77(Suppl):A866. Acknowledgement: We thank the patients who participated. This study was funded by UCB Pharma, conducted by Hummingbird, medical writing by Rohini Bose, Costello Medical, Singapore. Disclosure of Interests: Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Claire Barrett Grant/research support from: Nil, Consultant for: Nil, Speakers bureau: Nil, Yuji Hirano: None declared, Kei Ikeda: None declared, Kathy Paizis Speakers bureau: Alexion- SOMANZ breakfast session Cairns 2018 Thrombotic microangiopathy and pregnancy - $ 1300 Alexion – Meeting presentation aHUS and pregnancy June 2018 Autoimmune disease in pregnancy Nov 2018 UCB $550 pending, Azusa Sameshima: None declared, Yu-Jih Su: None declared, Carine Saadoun Employee of: UCB Pharma, Priscilla C Wong: None declared